Microplastics' occurrence, distribution, and chemical toxicity in backwater sediments from Puducherry Coast, Southeast India (Kuwait Journal of Science)
Microplastics (MPs) are degraded particles (≤5.0 mm) that originate from macro-sized plastics that significantly impact ecosystems due to their extensive fragmentation. These lighter particles, impacted by various environmental factors, become negatively buoyant and sink into sediments. In the current study, the vertical distribution of MPs from three distinct locations along the Puducherry coastal region, Ariyankuppam River Bridge (S1), Thengaithittu Fishing Harbor (S2), and Chunnambar Beach (S3), was investigated. The three sediment core samples ranging from 0 to 10 cm depth were bifurcated into five sub-samples of 2 cm intervals. The MPs exhibited a gradually decreasing abundance with increasing depth. Higher MPs were observed within the top 0–2 cm sediment samples. The average MP concentration in S1, S2, and S3 sediments was 138.5 MP cm−2, 107.5 MP cm−2, and 118.0 MP cm−2, respectively. The most dominant MPs identified in sediments were fibers, fragments, and film with the major composition of polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET). The MPs exhibited morphological changes, including irregular cracks, micro-brittles, pores, and erosion-like amorphous characteristics, potentially threatening marine organisms. Samples from S1 had a high pollution risk index (1,25,230) and polymeric hazards. All the sampling sites recorded a high contamination factor (CF ≥ 6) of sediments due to high levels of MPs. The present study emphasizes the need for deeper sediment sampling to gain valuable insights into MPs within global budgets. © 2025 The Authors